Appraisals of Salient Visual Elements in Web Page Design - Johanna M. Silvennoinen; Jussi P. P. Jokinen (Advances in Human-Computer Interaction)
Visual elements in user interfaces elicit emotions in users and are, therefore, essential to users interacting with different software. Although there is research on the relationship between emotional experience and visual user interface design, the focus has been on the overall visual impression and not on visual elements. Additionally, often in a software development process, programming and general usability guidelines are considered as the most important parts of the process. Therefore, knowledge of programmers’ appraisals of visual elements can be utilized to understand the web page designs we interact with. In this study, appraisal theory of emotion is utilized to elaborate the relationship of emotional experience and visual elements from programmers’ perspective. Participants (N=50) used 3E-templates to express their visual and emotional experiences of web page designs. Content analysis of textual data illustrates how emotional experiences are elicited by salient visual elements. Eight hierarchical visual element categories were found and connected to various emotions, such as frustration, boredom, and calmness, via relational emotion themes. The emotional emphasis was on centered, symmetrical, and balanced composition, which was experienced as pleasant and calming. The results benefit user-centered visual interface design and researchers of visual aesthetics in human-computer interaction.